2022
DOI: 10.3390/ijerph19116764
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Strength Recovery Measured by Isokinetic Dynamometer Technology after Anterior Cruciate Ligament Reconstruction Using Quadriceps Tendon Autografts vs. Hamstring Tendon Autografts or Patellar Tendon Autografts

Abstract: Background: This systematic review and meta-analysis compared the isokinetic strength of the muscular knee joint between quadriceps tendon autografts (QTAs) and hamstring tendon autografts (HTAs) or patellar tendon autografts (PTAs) after anterior cruciate ligament (ACL) reconstruction by determining the isokinetic angular velocity and follow-up time points. The functional outcomes and knee stability at the same time points were also compared using isokinetic technology. Methods: Two independent reviewers sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 54 publications
0
12
0
9
Order By: Relevance
“…Of the 2598 studies initially identified from the search strategy, a total of 50 systematic reviews (36 systematic reviews with meta‐analyses, 14 systematic reviews alone) were included in the final quality assessment (Figure 1) [1‐7, 10‐13, 16, 19, 21‐23, 25‐29, 31‐33, 35, 38‐42, 44, 46, 48, 52, 54, 58‐60, 65‐69, 71‐75, 77]. Cohen's κ Scores were 0.73, 0.75 and 0.74 at the title/abstract, full‐text screening and AMSTAR‐2 assessment stages, respectively, indicating substantial agreement at all phases of the review.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 2598 studies initially identified from the search strategy, a total of 50 systematic reviews (36 systematic reviews with meta‐analyses, 14 systematic reviews alone) were included in the final quality assessment (Figure 1) [1‐7, 10‐13, 16, 19, 21‐23, 25‐29, 31‐33, 35, 38‐42, 44, 46, 48, 52, 54, 58‐60, 65‐69, 71‐75, 77]. Cohen's κ Scores were 0.73, 0.75 and 0.74 at the title/abstract, full‐text screening and AMSTAR‐2 assessment stages, respectively, indicating substantial agreement at all phases of the review.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, incidence of post‐operative septic arthritis after RACLR has been found to be lower with QT compared to HT [55]. Previously described extensor mechanism strength deficits associated with QT harvest appear less pronounced than originally thought; and while extensor strength is inferior to HT at 6 months, strength measurements are equivalent at 1 year [23, 29]. While concerns exist regarding a double hit to the extensor mechanism when using a BTB graft followed by a QT graft or vice versa, multiple studies have demonstrated there is no appreciable difference in extension strength with or without a use of a second extensor mechanism graft in RACLR [26, 56].…”
Section: Discussionmentioning
confidence: 99%
“…The goal is to ensure safe return to sport and work, as inadequate strength has been associated with poorer function, altered biomechanics, and an increased risk of further knee injury [ 38 , 116 , 138 ]. Isokinetic strength testing is considered the “gold-standard” for postoperative strength testing, however varied testing protocols limit the comparability of studies [ 43 ]. When comparing different graft options, recent systematic reviews and meta-analyses demonstrate different outcomes [ 56 ].…”
Section: Introductionmentioning
confidence: 99%